Precarization of Young Indonesian Journalists During the Covid-19 Pandemic - Wisnu Prasetya Utomo (Komunikator, 2023)
This article discusses the working conditions and vulnerabilities young journalists face in Indonesia during the Covid-19 pandemic. Drawing on in-depth interviews with ten young journalists, it explores the experiences and working conditions faced by young journalists during the pandemic. Through the lens of precarization, this article demonstrates how young journalists are exposed to multiple precarity in the media industry. They entered an industry amid a disruption phase that began before the pandemic, and the pandemic worsened the condition. The result shows that young journalists are under the shadow of precarity in performing their work.